The impact of COVID-19 pandemic on treatment adherence, access to care, and disease control in diabetic patients in Jordan, an online survey - Ghaith M. Al-Taani, Suhaib M. Muflih, Rawan Alsharedeh, Reema Karasneh, Sayer I. Al-Azzam (Journal of Applied Pharmaceutical Science, 2024)
This study aimed to assess the impact of the COVID-19 pandemic on treatment adherence, access to care, and disease control in diabetic patients. Methods: An online survey design was utilized to collect data from a convenient sample of diabetic patients in Jordan. The developed survey collected data on sociodemographic characteristics, COVID-19 impact on access to care in diabetic patients, COVID-19 impact on diabetic patients’ adherence to their medications, and patients’ level of knowledge of COVID-19 impact on their health. Results: Nearly three-quarters of the participants reported that they avoided going to the physician for regular non-emergent visits during the outbreak, and 69.5% stated that their access to insulin, other diabetic medications, and supplies was not affected by the pandemic situation. The majority of patients reported that COVID-19 did not affect their adherence to their medications. Almost 42% reported that COVID-19 has negatively affected their physical activity level and their healthy lifestyle habits, while 60% stated that it did not affect their diet. Additionally, 56.6% reported that they have noticed less control in their blood glucose readings. Conclusion: The findings may reflect that the patients high adherence rate to their medications and that they avoided going to the doctor’s clinic to avoid contracting the virus.
Keywords: Diabetes mellitus, COVID-19, medications’ adherence, access to care